Long-term athletic development across different age groups and gender from Portuguese basketball players - Leite, N. M. C.; Sampaio, J. E. (International Journal of Sports Science and Coaching, 2012)
One of the main purposes of this study was to examine the quantity and type of sporting activities involved in acquiring high levels of basketball proficiency. Through a previously validated questionnaire, a sample composed of Portuguese basketball players (n = 1170) provided detailed information about the quantity and type of sporting activities undertaken throughout their sports career. The results suggested that players involved in the WIN stage had an earlier start in sport (p <.01) and a later specialization in basketball (p <.01). Time dedicated to all forms of practice and training in every developmental stage contributed to differentiate the players under examination as the WIN groups reported spending higher amounts of hours per week involved in those activities, in every stage of athletic development (p <.01). The results of this study allowed identifying differences in basketball development programs according to gender and should influence coaches` intervention in talent identification and early development of elite basketball players.